Oral Health in Athletes: An Overlooked Determinant of Performance, Recovery, and Safety - Lewalski, Tymon; Słuchocka, Joanna; Florczyk, Martyna; Lewalski, Oskar; Płuciennik, Lidia; Jeruć, Klaudia (Quality in Sport, 2026)
Oral health has traditionally occupied a peripheral role in sports medicine, yet the available evidence suggests that this separation is artificial. Across Olympic, professional, academy and university settings, athletes show a substantial burden of preventable oral disease, including dental caries, erosive tooth wear, gingivitis, periodontitis and sports-related dental trauma. The issue matters for more than comfort or appearance. Pain, chewing difficulty, disturbed sleep, reduced confidence, altered nutritional intake, missed training time and self-reported decrements in performance have all been described. In addition, chronic periodontal inflammation may contribute to a systemic inflammatory load that is biologically plausible in relation to recovery and physical readiness, although causality and the size of the effect remain incompletely defined. This feature review summarizes the current literature on oral health in athletes, with a focus on epidemiology, athlete-specific risk factors, mechanisms linking oral disease with performance and recovery, and practical prevention strategies for clubs, federations and individual competitors. The strongest evidence supports three messages. First, oral disease is common in elite and professional sport, often despite regular contact with health services. Second, the causes are multifactorial: frequent carbohydrate exposure, acidic sports products, exercise-related dry mouth, demanding schedules, variable dental attendance, and sport-specific injury risk all contribute. Third, prevention is realistic. Regular screening, fluoride-based caries prevention, individualized nutritional counselling, better management of periodontal inflammation, and broader adoption of custom-made mouthguards in high-risk sports can reduce disease burden without compromising performance. Oral health should therefore be treated as a core component of athlete welfare, readiness and long-term sporting sustainability, rather than an optional extra.